Education in Belarus in the interwar period: the Polish language as one of the official languages - Kozhinowa, Alla (Poznańskie Studia Slawistyczne, 2024)
The article focuses on education in the Belarusian Soviet Socialist Republic in the interwar period taking into account the fact that four languages were recognized as official at that time: Belarusian, Russian, Yiddish and Polish. Particular attention is paid to using Polish in the education system. The article comes to the following conclusions: the Polish language functioning in the education process was directly dependent on the policies of the socialist state, the status of other languages, and, first of all, Belarusian. This functioning was also influenced by the changing relations with the Republic of Poland. As in the case of other languages (apart from Russian), the language diversity increase was interrupted by a sharp turn, as a result of which, after World War II, education conducted in Polish in the BSSR was destroyed. Currently, after temporary rapid development during the perestroika period, any intention regarding the Polish language is systematically interrupted by the Belarusian authorities.